Neoliberalismo e (neo)autoritarismo: uma perspectiva de longo prazo a partir de casos do cone sul da América Latina - Ramírez, Hernán (2020)
Neoliberalism was implemented as public policy for the first time in the authoritarian regimes of the Southern Cone of Latin America, with the Chilean case as emblematic. It was there that his great experience was born, the one that told including the goodwill of Friedrich Hayek, Milton Friedman and James Buchanan (MEADOWCROFT; RUGER, 2014). He is not born with dictatorships, it is a project that had been going on for a long time, but it only takes shape with them as instruments.